Development of Student Worksheets Based Project Based Learning to Improve High-Level Thinking Skills (Hots) on Magnetic Material - Nona Omanda; Fauziyah Harahap; Yasaratodo Wau (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to develop LKPD based project-based learning to improve the validity of high-level, practical, and effective high-thinking skill. Learning products that are developed in the form of Students worksheets based on project learning. This type of research is the development of research and development (R&D) using the 4-D development model that developed by Thiagarajan. Data collected using expert validation, observation sheet, questionnaire response learners and teachers, and high-level thinking skills test. The results showed that LKPD based project- based learning in the valid and worthy category in use, the results of the validation of the material experts in stage I dan II are equal 76,47 % and 84% included into a very valid category, on the validation of the design expert design I and II is equal 81% dan 97% included in a very valid category, then on validation of language experts in stage I and II 62,50% and 90,62% located in a very valid category. LKPD based project-based learning has fulfilled aspects of effectiveness look at the various tests that have been done and declare that LKPD worth to use.